Aerospace dermatology - Sandeep Arora (Indian Journal of Dermatology, 2017)
Evolutionarily, man is a terrestrial mammal, adapted to land. Aviation and now space/microgravity environment, hence, pose new challenges to our physiology. Exposure to these changes affects the human body in acute and chronic settings. Since skin reflects our mental and physical well-being, any change/side effects of this environment shall be detected on the skin. Aerospace industry offers a unique environment with a blend of all possible occupational disorders, encompassing all systems of the body, particularly the skin. Aerospace dermatologists in the near future shall be called upon for their expertise as we continue to push human physiological boundaries with faster and more powerful military aircraft and look to colonize space stations and other planets. Microgravity living shall push dermatology into its next big leap-space, the final frontier. This article discusses the physiological effects of this environment on skin, effect of common dermatoses in aerospace environment, effect of microgravity on skin, and occupational hazards of this industry.